Access to primary healthcare during lockdown measures for COVID-19 in rural South Africa: an interrupted time series analysis. Issue 10 (5th October 2020) - Siedner, Mark J; Kraemer, John D; Meyer, Mark J; Harling, Guy; Mngomezulu, Thobeka; Gabela, Patrick; Dlamini, Siphephelo; Gareta, Dickman; Majozi, Nomathamsanqa; Ngwenya, Nothando; Seeley, Janet; Wong, Emily; et al.
Abstract : Objectives: We evaluated whether implementation of lockdown orders in South Africa affected ambulatory clinic visitation in rural Kwa-Zulu Natal (KZN). Design: Observational cohort Setting: Data were analysed from 11 primary healthcare clinics in northern KZN. Participants: A total of 46 523 individuals made 89 476 clinic visits during the observation period. Exposure of interest: We conducted an interrupted time series analysis to estimate changes in clinic visitation with a focus on transitions from the prelockdown to the level 5, 4 and 3 lockdown periods. Outcome measures: Daily clinic visitation at ambulatory clinics. In stratified analyses, we assessed visitation for the following subcategories: child health, perinatal care and family planning, HIV services, non-communicable diseases and by age and sex strata. Results: We found no change in total clinic visits/clinic/day at the time of implementation of the level 5 lockdown (change from 90.3 to 84.6 mean visits/clinic/day, 95% CI −16.5 to 3.1), or at the transitions to less stringent level 4 and 3 lockdown levels. We did detect a >50% reduction in child healthcare visits at the start of the level 5 lockdown from 11.9 to 4.7 visits/day (−7.1 visits/clinic/day, 95% CI −8.9 to 5.3), both for children aged <1 year and 1–5 years, with a gradual return to prelockdown within 3 months after the first lockdown measure. In contrast, we found no drop in clinic visitation in adults at the start of the level 5 lockdown, or related to HIV care (from 37.5 to 45.6, 8.0 visits/clinic/day, 95% CI 2.1 to 13.8). Conclusions: In rural KZN, we identified a significant, although temporary, reduction in child healthcare visitation but general resilience of adult ambulatory care provision during the first 4 months of the lockdown. Future work should explore the impacts of the circulating epidemic on primary care provision and long-term impacts of reduced child visitation on outcomes in the region.